2020
DOI: 10.1002/adhm.201901683
|View full text |Cite
|
Sign up to set email alerts
|

Osmosis‐Powered Hydrogel Microneedles for Microliters of Skin Interstitial Fluid Extraction within Minutes

Abstract: open-flow microperfusion, are time-consuming, cumbersome, patient-unfriendly, requiring medical expertise and specialized equipment. [2] Microneedles (MNs) have then been proposed for the extraction of skin ISF due to their minimally invasive and easy-to-administrated properties. [3,4,5] Hydrogel-based swellable MNs are especially attractive because of their simplicity, efficiency, and biocompatibility. Samant et al. recently showed that polyvinyl alcohol (PVA)-based hydrogel patch could collect ISF from ex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
153
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 34 publications
2
153
0
Order By: Relevance
“…Zheng et al demonstrated faster extraction of ISF (3 folds) comparing with the existing platform. The team devised an osmolyte powered patch of 100 MNs array [66]. The MNs array was fabricated by a composition of osmolytes (maltose) and hydrogel (methacrylated hyaluronic acid) materials.…”
Section: Microneedlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zheng et al demonstrated faster extraction of ISF (3 folds) comparing with the existing platform. The team devised an osmolyte powered patch of 100 MNs array [66]. The MNs array was fabricated by a composition of osmolytes (maltose) and hydrogel (methacrylated hyaluronic acid) materials.…”
Section: Microneedlesmentioning
confidence: 99%
“…Hydrogel are liquid-swollen materials that are good candidate for ISF extraction [66,90,134]. Hydrogel MNs swell by ISF absorption without dissolution in the skin [135,136].…”
Section: Hydrogel Mnsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional methods for ISF extraction, such as a suction blister, depth-limited hypodermic cannula, and open-ow microperfusion, are time-consuming, risky to patients, demanding medical expertise and specialized instrument 9-11 . To address the issues, microneedles (MNs) have been proposed to extract skin ISF with a painless and minimally invasive strategy. MNs are fabricated from metal or polymer with hundreds of microns in length and penetrate the main barrier of the skin, stratum corneum, thereby creating a pathway accessible to skin ISF 2,13,14 . The style of MN can be designed depending on the applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a lateral ow strip can detect a target such as food poisoning bacteria with the naked eye by coloring reaction without expensive detection equipment [20][21][22] . Most of all, metal MNs including the paper reservoir, were reported to extract ISF at a rate of 2 to 4 µL per minute under in vivo conditions, which is faster than that of hydrogel MN 3,[13][14][15][16] It is essential to improve the diagnosis sensitivity by securing the stability of biomarkers and a su cient quantity of samples to minimize diagnostic errors such as false positives and false negatives 23,24 .…”
Section: Introductionmentioning
confidence: 99%